Examining the causal relationship between globalization and energy consumption inMINTcountries: Evidence from bootstrap panel granger causality - Fahimi, Amin; Olasehinde-Williams, Godwin; Akadiri, Seyi Saint (Wiley, 2021)
This paper examines the causal relationships between globalization and energy consumption for MINT member countries (Mexico, Indonesia, Nigeria and Turkey) over the period 1970-2015, while controlling for the effect of gross domestic product. To control for common unobserved shocks and country-specific heterogeneity inherent in panel data analyses, we employ the cross-sectional augmented ADF and IPS tests to confirm the panel stationarity properties. We test for causal relations at country and panel levels through the Emirmahmutoglu & Kose, Economic Modelling, 2011, 28(3), 870-876 panel causality test for heterogeneous mixed panels. The causality results show that globalization is strongly related to energy consumption in MINT countries. Specifically, at the country level, we detect feedback causality between globalization and energy consumption in Indonesia, Nigeria and Turkey, and find unidirectional causality running from globalization to energy consumption in Mexico. At the panel level, we also detect feedback causality between both variables. In general, our results lend credence to previous findings on globalization-driven energy consumption hypothesis for MINT countries. Useful policy insights are also provided on the basis of our findings.
Keywords: Energy consumption; globalization; granger causality; MINT countries; panel data